Married by mistake - Stacey, Shannon (Stacey, Shannon. Sutton's Place., 2023)
"When sworn enemies Chelsea Grey and John Fletcher travel to Las Vegas for a friend's wedding, the last thing they anticipate is waking up married themselves. Unfortunately, disentangling their wedding knot proves more complicated than they'd hoped. With Christmas fast approaching, the feisty barista and her coffee-hating "hubby" are still living under one roof -- and wondering why their temporary marriage is suddenly feeling suspiciously like the real thing ..."--